Social Order and the Limits of Law - IREDELL IENKINS (Princeton University Press, 2014)
THIS BOOK has a double intention. It means first to develop a systematic theory of positive law, with close attention to the circumstances that bring law into being, the purposes that law is intended to serve, and the structure of a legal system. Second, it proposes to apply this theory to an examination of the problems that law faces and the conditions that it must satisfy if it is to be an effective force in society. The earlier part of the book is therefore devoted to the formulation of a general theory of law. The first and most important step in this enterprise is to place law within the total environment from which it emerges as an operative element, and from which it derives its nature and functions. All of the contents that law deals with and all of the ends that it serves have both their original and their eventual loci in extralegal sources: they issue from and refer to things, forces, situations, needs, and purposes that are independent of and prior to law itself. As an explicit and organized mode of administering man's affairs, law is a late emergent that serves generally to extend and refine the reach of already existent ideas and institutions. This insight has been too widely recognized to be announced as a discovery. It has served as the common point of departure for radically divergent lines of thought. The schools of historical, sociological, and psychological jurisprudence, the adherents of natural law doctrine, the legal pragmatists and realists, those who regard law as an instrument of political power and those who view it as an agent of policy formulation— all of these agree that the path to an understanding of the law leads through a study of the larger context from which law inherits its facts, its goals, and its problems. However, the crucial element in any such study is the context in which law is examined. The various schools of thought mentioned above have contributed greatly to our knowledge both of the multiple facets of law and of the intricate interplay of law with life. But they have also been somewhat specialized in their focus and isolated from one another, so that their collective impact is a series of fragmented insights rather than a coherent vision. What is now desirable, I would suggest, is a speculative approach that seeks a synthesis of the available scholarship and that attempts to reach a systematic theory of the origins and ends of law and of the essential structure of the legal order.